2021
DOI: 10.1111/tri.14005
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver disease in living liver donors: a single‐institute experience of 220 donors

Abstract: Summary We retrospectively reviewed 220 living liver donors, with a focus on the development of postoperative fatty liver. Data regarding demographics, comorbidities, imaging tests, operations and biopsies were obtained from medical records. We used unenhanced CT and USG to diagnose fatty liver. Donor candidates with fatty liver underwent weight loss intervention until imaging tests no longer demonstrated any features of fatty liver. Among 220 donors, 61 were diagnosed with preoperative fatty liver. The mean B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In this study, we demonstrated that 14.2% of living donors developed fatty liver after donation hepatectomy. Consistently, recent single‐institution studies in Japan revealed that the incidence of fatty liver in the living donor after donation hepatectomy was 3.8%–14.5% 12,13 . In the general population, a cross‐sectional study of Japanese adults ( n = 11 714) revealed NAFLD in 20.4% of subjects 14 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In this study, we demonstrated that 14.2% of living donors developed fatty liver after donation hepatectomy. Consistently, recent single‐institution studies in Japan revealed that the incidence of fatty liver in the living donor after donation hepatectomy was 3.8%–14.5% 12,13 . In the general population, a cross‐sectional study of Japanese adults ( n = 11 714) revealed NAFLD in 20.4% of subjects 14 .…”
Section: Discussionsupporting
confidence: 54%
“…Consistently, recent single‐institution studies in Japan revealed that the incidence of fatty liver in the living donor after donation hepatectomy was 3.8%–14.5%. 12 , 13 In the general population, a cross‐sectional study of Japanese adults ( n = 11 714) revealed NAFLD in 20.4% of subjects. 14 Another study of 8352 adult subjects who received a health checkup revealed that the prevalence of NAFLD was 29.7%.…”
Section: Discussionmentioning
confidence: 99%
“…According to results reported using the Clavien-Dindo classification, the frequency of life-threatening complications was minimal [27, 33], and hepatobiliary complications were reported in approximately 2~18% of cases [27,34]. Nevertheless, some donors may require medical treatment or prolonged hospitalization [35][36][37], which can reduce health-related quality of life [38] and threaten mental health, such as the development of anxiety or alcohol use disorders [7]. Donor safety after surgery is of utmost importance [39].…”
Section: Discussionmentioning
confidence: 99%
“…The controlled attenuation parameter (CAP) is a novel ultrasound-based elastography method for detection of the grade of steatosis, an important parameter in the assessment of a liver donor, and mainly associated with male sex and high body mass index [ 32 ].…”
Section: New Ultrasound Techniques In Liver Transplantationmentioning
confidence: 99%